2023
DOI: 10.1007/s00520-023-07698-3
|View full text |Cite|
|
Sign up to set email alerts
|

Under recognition and treatment of lymphedema in head and neck cancer survivors – a database study

Abstract: Purpose: Head and neck cancer (HNC) will be diagnosed in approximately 54,000 Americans in 2022 with more than 11,000 dying as a result. The treatment of HNC often involves aggressive multimodal therapy including surgery, radiotherapy, and systemic therapy. HNC and its treatments are associated with multiple painful and function-limiting neuromusculoskeletal and visceral long-term and late effects. Among these is head and neck lymphedema (HNL), the abnormal accumulation of protein rich uid, in as many as 90% o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…Chronic aspiration is a life-threatening manifestation of dysphagia, affecting 30% of HNC survivors treated with irradiation [ 14 ]. RAD is not only caused by RIF of the cervical region (e.g., strap muscles, intrinsic laryngeal musculature, recurrent laryngeal nerve, and lymphatics) [ 7 , 9 , 15 ] but also by sensory deficits associated with cranial nerve neuropathies caused by radiation-induced hypoxia [ 8 , 16 ]. Tedla et al [ 7 ] demonstrated that swallowing dysfunction after irradiation is caused, at least partially, by a reduction in intrinsic laryngeal muscle mass and by changes in the laryngeal nerves in human models, which are involved in aspiration prevention.…”
Section: Discussionmentioning
confidence: 99%
“…Chronic aspiration is a life-threatening manifestation of dysphagia, affecting 30% of HNC survivors treated with irradiation [ 14 ]. RAD is not only caused by RIF of the cervical region (e.g., strap muscles, intrinsic laryngeal musculature, recurrent laryngeal nerve, and lymphatics) [ 7 , 9 , 15 ] but also by sensory deficits associated with cranial nerve neuropathies caused by radiation-induced hypoxia [ 8 , 16 ]. Tedla et al [ 7 ] demonstrated that swallowing dysfunction after irradiation is caused, at least partially, by a reduction in intrinsic laryngeal muscle mass and by changes in the laryngeal nerves in human models, which are involved in aspiration prevention.…”
Section: Discussionmentioning
confidence: 99%
“… 1 However, a retrospective study based on an integrated US healthcare database showed that only 6.5% of head and neck cancer survivors were diagnosed as HNL, and merely 3% of head and neck cancer survivors received lymphedema treatment, implying that HNL was underdiagnosed and undertreated. 2 The first-line therapy for HNL, according to the American Cancer Society head and neck cancer survivorship care guideline, is manual lymphatic drainage (MLD). 3 Currently, the most commonly used treatment for HNL is complete decongestion therapy (CDT), including MLD, customized compression garments, physical exercise, and skin care.…”
Section: Introductionmentioning
confidence: 99%
“…5 Reports indicate an increasing prevalence of lymphedema following HNC therapy, with some studies stating the presence of lymphedema in up to 90% of survivors. 6,7 While most reports of lymphedema have been associated with patients treated with multimodal therapy in breast cancer, the addition of radiation therapy to surgical treatment has been found to increase lymphedema risk, suggesting that radiation may play an important role in lymphedema development. 8,9 In addition, several factors have been found to be correlated with lymphedema development in HNC patients treated with multiple modalities.…”
Section: Introductionmentioning
confidence: 99%